The right of access to justice of indigenous populations in the Inter-American Human Rights System - Díaz Lafuente, José (REVISTA ELECTRONICA IBEROAMERICANA, 2023)
In Latin America, there are between 41.8 and 53.4 million indigenous people, 45.5% are poor and 7.1% are extremely poor. Access to justice represents an essential dimension of any democratic State and a fundamental requirement for the effective enjoyment of the other human rights and public freedoms. However, in practice, indigenous populations face situations of structural inequality and systemic socioeconomic, political and cultural discrimination that hinder their equal access to effective judicial remedies. From the necessary consideration of indigenous specificity and respect for cultural diversity, and applying a gender and intersectional approach, this paper focuses on the analysis of the progressive recognition in the inter-American human rights system of the right of indigenous populations to access to justice, paying special attention to the most innovative and guaranteeing elements highlighted by the specialized doctrine, by the reports and opinions of the Inter-American Commission on Human Rig nd by the extensive jurisprudence of the Inter-American Court of Human Rights.
Keywords: Indigenous populations; access to justice; Inter-American Human Rights System